A clinical study on the efficacy and safety of poly-herbal formulation in managing functional dyspepsia - Debasish Hota; Anand Srinivasan; Manas Kumar Panigrahi; Snigdha Suman Dalua; Poorva Tiwari; Ramachandran Valavan (Phytomedicine Plus)
Introduction: Functional dyspepsia is a common condition that affects millions of people worldwide. It is characterized by symptoms such as abdominal discomfort, bloating, and nausea, which can significantly impact a person's quality of life. While there are several pharmaceutical treatments available, many individuals are turning to herbal remedies as a safer and more natural alternative. This clinical study aimed to evaluate the efficacy and safety of poly-herbal formulation (PHF), marketed under brand names like Dizester® Herbal, Great Day®, etc. in patients suffering from functional dyspepsia compared to Pantoprazole, a commonly used pharmaceutical treatment. Materials & Methods: The study included 80 patients, with 40 patients in each treatment arm. The primary objective was to assess the improvement in symptoms using various questionnaires at All India Institute of Medical Science Bhubaneswar, including the Reflux Disease Questionnaire, Short-Form Leeds Dyspepsia Questionnaire, GERD-Health Related Quality of Life Questionnaire, visual analogue scale (VAS) for pain, and Investigator's Symptomatic Assessment. The secondary objective was to evaluate the safety of PHF by assessing liver and renal function parameters and hemogram. Results & discussion: The results showed significant improvement in symptoms of GERD in the PHF group, which was comparable to the Pantoprazole group. The burning feeling behind the breastbone, pain behind the breastbone, burning feeling in the center of the upper stomach, acid taste in the mouth, and unpleasant movement of material upwards towards the mouth improved significantly from the beginning of the study to the follow-up visits. The mean VAS score reduced by 71.5 % in the PHF arm and 67.85 % in the Pantoprazole arm. Additionally, the study found no abnormal elevations in liver and renal function parameters in blood or any abnormal changes in hemogram, indicating the safety for use in patients with functional dyspepsia. Since the synthetic anti-dyspeptic drugs like proton pump inhibitors are known to have adverse effects, this natural alternative PHF shows promising results in a safer way. Conclusion: In conclusion, this study provides evidence for the efficacy and safety of PHF in improving symptoms of functional dyspepsia. The use of synthetic anti-dyspeptic medications has been associated with the occurrence of undesirable effects. In light of this, PHF has demonstrated encouraging outcomes in a manner that is considered safer.